2019
DOI: 10.47197/retos.v38i38.73450
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la ansiedad competitiva en jugadores jóvenes de waterpolo en función del género y rendimiento (Analysis of competitive anxiety in young water polo players according to gender and performance)

Abstract: El objetivo de este estudio fue analizar la relación entre ansiedad competitiva en jóvenes jugadores de waterpolo y su rendimiento atendiendo al género y clasificación. La muestra estuvo formada por 268 waterpolistas infantiles (102 niñas y 166 niños) que participaron en el Campeonato de España Infantil masculino y femenino por Federaciones Autonómicas. Se ha utilizado la versión adaptada al español de la Escala de Ansiedad Competitiva (SAS-2) para la medición de la ansiedad. Se hallan diferencias significativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…At a sports level, Borges et al (2020) indicate that competition represents a challenge, which can be a source of activation or the origin of alterations for the athlete. In this sense, there are various variables that affect the perceptions of athletes in one way or another (e.g.…”
Section: Competitive Anxiety and Main Study Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…At a sports level, Borges et al (2020) indicate that competition represents a challenge, which can be a source of activation or the origin of alterations for the athlete. In this sense, there are various variables that affect the perceptions of athletes in one way or another (e.g.…”
Section: Competitive Anxiety and Main Study Variablesmentioning
confidence: 99%
“…Thus, the importance of competitive anxiety for children has been examined, leadoing to an increase in the number of studies linked to this theme (Arnau et al, 2018;Bohórquez and Checa, 2017;Bois et al, 2009;Borges et al, 2020;García-Mas et al, 2011;Grossbard et al, 2007;Grossbard et al, 2009;Pérez-Cáceres et al, 2021;Pluhar et al, 2019;Ramis et al, 2013). High levels of competitive anxiety are presented as a predictor of abandoning sports practice and are associated with low performance and less enjoyment (Gould et al, 1985;Scanlan et al, 2005;Smith and Smoll, 1991).…”
Section: Competitive Anxiety and Main Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research finds higher averages for worry, deconcentration and global anxiety in the group of women compared to the group of men in samples of competitive athletes [37][38][39][40][41]. Borges et al [42], in their study of adolescent water polo players, found higher scores in males for both precompetitive anxiety and competitive anxiety. The authors explain this finding based on the important maturational and psychobiological differences that exist between both sexes at puberty and adolescence.…”
Section: Anxiety Depression and Self-esteem In Sportsmentioning
confidence: 99%
“…De este modo, parece que los hombres entienden como facilitadores los síntomas de la ansiedad percibidos y a la vez tienen niveles de autoconfianza más altos que las mujeres (Menéndezs, 2020;Sámano, 2020). Sin embargo, en otros estudios no se han hallado diferencias en los niveles de ansiedad independientemente del sexo del deportista (Borges et al, 2020;Guillén y Álvarez-Malé, 2010).…”
Section: Introductionunclassified